AVALIAÇÃO DA ATIVIDADE ANTIBACTERIANA E ANTIADERENTE DO ÓLEO ESSENCIAL DE Lavandula hybrida grosso CONTRA Pseudomonas aeruginosa (REMUNOM, 2024)
Bacterial resistance has increased over time, since each person's oral microbiota is different and the number of microorganisms that colonize the human body can be 10 times greater than the number of cells of the individual. In this middle ground, alternatives have emerged such as the use of products of plant origin with low toxicity and good efficacy, which aim to prevent and combat various pathologies. This study aimed to evaluate the antibacterial and anti-adhesive activities of Lavandula hybrida grossoessential oil against Pseudomonas aeruginosa. This is a study on the essential oil of Lavandula hybrida grosso against Pseudomonas aeruginosa. The substance was solubilized in dimethyl sulfoxide (DMSO) and diluted in distilled water to carry out pharmacological tests. To carry out the present study, the clinical strain Pa 104 of Pseudomonas aeruginosa was used, which was maintained on Muller Hinton Agar (AMH) medium. To carry out this research, Minimum Inhibitory Concentration (MIC) techniques were used, which was determined by the microdilution technique in plates containing 96 sterile holes. And the Minimum Adhesion Inhibitory Concentration (CIMA), carried out in glass tubes, using a medium with 5% sucrose added. According to the present research, for the methodology used and for the strain under study, it was not possible to accurately determine the MIC value. Regarding non-stick activity, it was found that the essential oil used in the present research demonstrated better properties than 0.12% chlorhexidine digluconate. Therefore, it is concluded that the essential oil in question is an effective therapeutic option for the treatment of oral infections caused by this bacteria. However, further studies are essential to confirm its effectiveness and, subsequently, in vivo research to evaluate its behavior in the human body.  Keywords: Pharmacology; Phytotherapy; Dentistry.